Alternative end-joining originates stable chromosome aberrations induced by etoposide during targeted inhibition of DNA-PKcs in ATM-deficient tumor cells - de Campos Nebel, Ildefonso Marcelo (2022)
ATM and DNA-PKcs coordinate the DNA damage response at multiple levels following the exposure to chemotherapy. The Topoisomerase II poison etoposide (ETO) is an effective chemotherapeutic agent that induces DNA double-strand breaks (DSB), but it is responsible from the chromosomal rearrangements frequently found in therapy-related secondary tumors. Targeted inhibition of DNA-PKcs in ATM-defective tumors combined with radio- or chemotherapy has been proposed as relevant therapies. Here, we explored the DNA repair mechanisms and the genetic consequences of targeting the non-oncogenic addiction to DNA-PKcs of ATM-defective tumor cells after exposure to ETO. We demonstrated that chemical inhibition of DNA-PKcs followed by treatment with ETO resulted in the accumulation of chromatid breaks and decreased mitotic index in both A-T cells and ATM-knocked-down (ATMkd) tumor cells. The HR repair process in DNA-PKcs-inhibited ATMkd cells amplified the RAD51 foci number, with no correlated increase in sister chromatid exchanges. The analysis of post-mitotic DNA lesions presented an augmented number of persistent unresolved DSB, without alterations in the cell cycle progression. Long-term examination of chromosome aberrations revealed a strikingly high number of chromatid and chromosome exchanges. By using genetic and pharmacological abrogation of PARP-1, we demonstrated that alternative end-joining (alt-EJ) repair pathway is responsible for those chromosome abnormalities generated by limiting c-NHEJ activities during directed inhibition of DNA-PKcs in ATM-deficient cells. Targeting the non-oncogenic addiction to DNA-PKcs of ATM-defective tumors stimulates the DSB repair by alt-EJ, which is liable for the origin of cells carrying stable chromosome aberrations that may eventually restrict the therapeutic strategy.